Building valve amplifiers - Jones, Morgan (Newnes, 2014)
Building Valve Amplifiers is a unique hands-on guide for anyone working with tube audio equipment--as an electronics hobbyist, audiophile or audio engineer. This 2nd Edition builds on the success of the first with technology and technique revisions throughout and, significantly, a major new self-build project, worked through step-by-step, which puts into practice the principles and techniques introduced throughout the book. Particular attention has been paid to answering questions commonly asked by newcomers to the world of the valve, whether audio enthusiasts tackling the.
Includes bibliographical references and index. - Print version record
Keywords: Audio amplifiers -- Design and construction; Audio amplifiers -- Maintenance and repair; Audio amplifiers; Design and construction; Audio amplifiers; Maintenance and repair